Walnut green husk ethanol extract improves gut microbiota and their metabolites associated with NLRP3 in non-alcoholic steatohepatitis. Issue 11 (26th May 2022) - Fang, Qionglian; Li, Xinping; Wang, Mengmeng; Qiao, Xue; Huang, Feng; Hu, Chunyan; Xue, Yongmei; Zhao, Shenglan; Lin, Yuping
Abstract : Increasing studies have shown that walnut green husk (WGH) has obvious effects on reducing lipid, resisting oxidation, and protecting the liver. Abstract : Increasing studies have shown that walnut green husk (WGH) has obvious effects on reducing lipid, resisting oxidation, and protecting the liver. However, the mechanism by which WGH can prevent high-fat diet (HFD)-induced non-alcoholic steatohepatitis (NASH) remains unclear. This study is aimed at investigating the effects of WGH ethanol extract (WGHE) on NLRP3-related biochemical indicators and the diversity and metabolism of gut microbiota in HFD-induced NASH rats. WGHE was administered to HFD-induced NASH rats for 6 weeks. The results showed that WGHE could decrease the levels of blood and liver TC, TG, LDL-C, AST, and ALT and the levels of liver indices, including IL-1β, IL-6, TNF-α, TGF-β, FFA, VLDL, caspase-1, ASC, and NLRP3, while it could increase the levels of HDL-C. The pathological damage to liver tissues was significantly reduced. Moreover, WGHE could reduce the Firmicutes/Bacteroidetes (F/B) ratio and the relative abundances of potentially harmful bacteria, such as Lachnospiraceae and Christensenellaceae, and increase that of potentially beneficial bacteria, such as norank_f__Muribaculaceae. These bacteria were associated with NASH and most of them were significantly associated. A total of 23 gut bacteria and 31 metabolites were significantly altered by HFD, which was reversed by WGHE. The common functional pathways, including lipid metabolism and steroid biosynthesis, were identified through the analysis of KEGG metabolic pathways. In addition, the changes in gut microbiota, such as unclassified_f__Lachnospiraceae, unclassified_g__Blautia, and unclassified_g__Desulfovibrio, were associated with the changes in key intestinal metabolites, such as arachidonoyl amine, xanthine, and 25, 26-epoxy-1α-hydroxyvitamin D3. In conclusion, WGHE could mitigate HFD-induced NASH in rats by interfering with the NLRP3-related gut microbiota and their metabolites.